1988
DOI: 10.1084/jem.167.6.2017
|View full text |Cite
|
Sign up to set email alerts
|

(NZW x BXSB)F1 mouse. A new animal model of idiopathic thrombocytopenic purpura.

Abstract: There has recently been an increase in data indicating that autoimmune mechanisms are involved in the etiopathogenesis of idiopathic thrombocytopenic purpura (ITP) (1, 2). Although antibodies that react with platelets are found in most patients with ITP, the pathogenetic nature of the antibodies remains to be clarified . The discovery of an animal model for ITP has therefore been long-awaited. Here we have found that (NZW x BXSB)Fi (W/B Fi) mice, which develop lupus nephritis with myocardial infarction (3), sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(80 citation statements)
references
References 9 publications
5
75
0
Order By: Relevance
“…4 (NZW ϫ BXSB)F1 mice spontaneously produce antiplatelet autoantibodies, leading to thrombocytopenia in the context of a complex autoimmune syndrome dissimilar to organspecific ITP. 5 Production of antiplatelet autoantibodies through molecular mimicry may be studied by immunizing mice with rat platelets, but the resulting thrombocytopenia is at best moderate and very transient in normal mice. 6 Here, we report on the effect of infection with the common mouse viruses lactate dehydrogenaseelevating virus (LDV) and mouse hepatitis virus (MHV), on platelet counts in mice with preexisting antiplatelet autoantibodies.…”
Section: Introductionmentioning
confidence: 99%
“…4 (NZW ϫ BXSB)F1 mice spontaneously produce antiplatelet autoantibodies, leading to thrombocytopenia in the context of a complex autoimmune syndrome dissimilar to organspecific ITP. 5 Production of antiplatelet autoantibodies through molecular mimicry may be studied by immunizing mice with rat platelets, but the resulting thrombocytopenia is at best moderate and very transient in normal mice. 6 Here, we report on the effect of infection with the common mouse viruses lactate dehydrogenaseelevating virus (LDV) and mouse hepatitis virus (MHV), on platelet counts in mice with preexisting antiplatelet autoantibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Idiopalhic thrombocylopenic purpuni (ITP) is a .syndrome which is caused by circulating antibodies that react with the platelet membrane [1.2], It is thought that platelet-associated IgG (PAlgG) has an important role in the mechanism of ITP, because an incrca.se in PAIgG is closely correlated with a deerease in the platelet count in this disease [1][2][3][4][5], Furthermore, high levels of PAIgM and platelet-associated complement component 3 (PAC3) are also considered to be of pathogenetic relevance to thrombocytopenia in ITP [2.6-9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that autoimmune diseases can be treated by BMT without immunosuppressants in animal models. 3,[29][30][31][32][33] Even in humans, the effects of BMT have also been reported. [34][35][36] Therefore, the simultaneous transplantation of BMCs plus PIs is an ideal therapy for T1DM, as the rejection of grafted PIs and autoimmune reaction to PIs can be prevented if BMT can be easily performed without the long-term usage of immunosuppressants.…”
Section: Discussionmentioning
confidence: 99%